Therapeutic Delivery of MicroRNA-29b by Cationic Lipoplexes for Lung Cancer - Yun Wu; Melissa Crawford; Yicheng Mao; Robert J Lee; Ian C Davis; Terry S Elton; L James Lee; Serge P Nana-Sinkam (Elsevier, 2013)
MicroRNA-29b (miR-29b) expression has been shown to be reduced in non-small-cell lung cancer (NSCLC) tissues. Here, we have identified the oncogene cyclin-dependent protein kinase 6 (CDK6) as a direct target of miR-29b in lung cancer. We hypothesized that in vivo restoration of miR-29b and thus targeting of genes important to tumor initiation and progression may represent an option for lung cancer treatment. We developed a cationic lipoplexes (LPs)-based carrier that efficiently delivered miR-29b both in vitro and in vivo. LPs containing miR-29b (LP-miR-29b) efficiently delivered miR-29b to NSCLC A549 cells, reduced the expression of key targets CDK6, DNMT3B, and myeloid cell leukemia sequence 1 (MCL1), as well as cell growth and clonogenicity of A549 cells. In addition, the IC50 for cisplatin in the miR-29b-treated cells was effectively reduced. In a xenograft murine model, LPs efficiently accumulated at tumor sites. Systemic delivery of LP-miR-29b increased the tumor miR-29b expression by approximately fivefold, downregulated the tumor mRNA expression of CDK6, DNMT3B, and MCL1 by ~57.4, ~40.5, and ~52.4%, respectively, and significantly inhibited tumor growth by ~60% compared with LP-miR-NC (negative control). Our results demonstrate that cationic LPs represent an efficient delivery system that holds great potential in the development of miRNA-based therapeutics for lung cancer treatment.